Can K-ras gene mutation be utilized as prognostic biomarker for colorectal cancer patients receiving chemotherapy? A meta-analysis and systematic review. - Yuan-Yi Rui; Dan Zhang; Zong-Guang Zhou; Cun Wang; Lie Yang; Yong-Yang Yu; Hai-Ning Chen (PLoS ONE, 2013)
Introduction K-ras gene mutations were common in colorectal patients, but their relationship with prognosis was unclear. Objective Verify prognostic differences between patient with and without mutant K-ras genes by reviewing the published evidence. Method Systematic reviews and data bases were searched for cohort/case-control studies of prognosis of colorectal cancer patients with detected K-ras mutations versus those without mutant K-ras genes, both of whom received chemotherapy. Number of patients, regimens of chemotherapy, and short-term or long-term survival rate (disease-free or overall) were extracted. Quality of studies was also evaluated. Principal findings 7 studies of comparisons with a control group were identified. No association between K-ras gene status with neither short-term disease free-survival (OR=1.01, 95% CI, 0.73-1.38, P=0.97) nor overall survival (OR=1.06, 95% CI, 0.82-1.36, P=0.66) in CRC patients who received chemotherapy was indicated. Comparison of long-term survival between two groups also indicated no significant difference after heterogeneity was eliminated (OR=1.09, 95% CI, 0.85-1.40, P=0.49). Conclusions K-ras gene mutations may not be a prognostic index for colorectal cancer patients who received chemotherapy.